Preparation process of high-purity nano aluminum oxide
By mixing the aqueous ammonium bicarbonate solution with polyethylene glycol, adjusting the pH with ammonia water, adding ammonium aluminum sulfate solution to the reaction system, aging and filtration, the existing method is solved by using the supercritical drying and high-temperature calcining of the autoclave. In the technology, the problem of complex preparation of nano alumina and low purity has achieved high efficiency and high purity preparation of nano alumina.
Patent Information
- Application Number
- CN202411612549.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nano alumina preparation methods have problems such as small production scale, high technical requirements, harsh equipment conditions, complex operation process, and difficult to control process parameters, making it difficult to efficiently prepare high-purity nano alumina.
Mix the aqueous ammonium bicarbonate solution and polyethylene glycol evenly, and adjust the pH to 9.3-9.4 with ammonia water. Add ammonium aluminum sulfate solution to drop to the reaction system to adjust the pH to 9.1-9.3. After aging and filtration, pass through an autoclave. Supercritical drying and high-temperature calcination produce high-purity nanoalumina.
The efficient preparation of high-purity nano-alumina is achieved, which improves the purity and particle size uniformity of nano-alumina, simplifies the process flow and reduces the operation complexity.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano materials, in particular to a preparation process of high-purity nano aluminum oxide. Background Art
[0002] Nano-alumina is an ultrafine particle with a size of 1 to 100 nm. It has a strong small size effect, quantum size effect, surface effect and macroscopic quantum tunneling effect. It shows a series of excellent properties in many aspects such as light, electricity, thermodynamics and chemical reactions. It is widely used as fine ceramics, composite materials, fluorescent materials, humidity-sensitive sensors and infrared absorption materials. So far, there are various methods for preparing nano-alumina, which can be divided into three categories: gas phase method, liquid phase method and solid phase method; but there are still many problems in these preparation methods, such as small production scale, high technical requirements, harsh equipment conditions, complex operation process, difficult control of process parameters and other shortcomings. How to simply and efficiently prepare high-purity nano-alumina is still a problem to be solved. Therefore, the present invention proposes a preparation process for high-purity nano-alumina to solve the above problems. Summary of the invention
[0003] The purpose of the present invention is to provide a preparation process of high-purity nano-alumina to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A preparation process of high-purity nano-alumina comprises the following steps: uniformly mixing an aqueous ammonium bicarbonate solution and polyethylene glycol, and adjusting the pH value to 9.3-9.4 with aqueous ammonia; dripping an ammonium aluminum sulfate solution into a reaction system, and then adjusting the pH value to 9.1-9.3 with aqueous ammonia; obtaining a precursor precipitate after aging and filtering; uniformly mixing the precursor precipitate with anhydrous ethanol to prepare a precursor alcohol sol; placing the precursor alcohol sol in an autoclave, and supercritically drying to obtain a nano-alumina precursor; and calcining the nano-alumina precursor at a high temperature to obtain the high-purity nano-alumina.
[0006] As an optimization, the preparation process of the high-purity nano-alumina includes the following preparation steps:
[0007] (1) Mixing ammonium bicarbonate aqueous solution and polyethylene glycol in a mass ratio of 1:(0.2-0.22), stirring at 10-30° C. and 300-500 r / min for 8-10 min, adjusting the pH to 9.3-9.4 with an ammonia solution, and adding aluminum ammonium sulfate solution 1.9-2.1 times the mass of the ammonium bicarbonate aqueous solution dropwise at a constant rate within 20 min at 10-30° C. and 500-600 r / min; after the titration is completed, stirring is continued for 2-3 h, adjusting the pH to 9.1-9.3 with an ammonia solution, and aging for 23-25 h; filtering, washing with anhydrous ethanol and deionized water for 5-7 times each, to obtain a precursor precipitate;
[0008] (2) The precursor precipitate and anhydrous ethanol are mixed uniformly in a mass ratio of 1:(2.0-2.2), and stirred at 10-30°C and 400-500r / min for 30-40min to obtain a precursor alcohol sol; the precursor alcohol sol is placed in an autoclave, and anhydrous ethanol is added to the autoclave to submerge it to 3 / 5 of the height of the steel pipe; the autoclave cover is covered, the air inlet pipe is connected to a nitrogen bottle, and the air outlet pipe is connected to a condenser, and nitrogen is passed to maintain the pressure at 7.4-7.6MPa, and then the gas is turned off; the air inlet and outlet switches are tightened, the power of the temperature controller is turned on, and the temperature is programmed to rise. After keeping the temperature for 30min, the ethanol gas is slowly released, and then the dry gel in the autoclave is purged with nitrogen until it cools to room temperature, the autoclave is opened, and the material is discharged to obtain a nano-alumina precursor; the nano-alumina precursor is placed in a high-temperature resistance furnace, calcined at high temperature, and cooled to room temperature to obtain high-purity nano-alumina.
[0009] As an optimization, the preparation method of the ammonium bicarbonate aqueous solution in step (1) is: ammonium bicarbonate and deionized water are mixed evenly to prepare an ammonium bicarbonate aqueous solution with a molar concentration of 2 mol / L.
[0010] As an optimization, the polyethylene glycol in step (2) is prepared by mixing two polyethylene glycols, PEG400 and PEG6000, in a mass ratio of 1:1.
[0011] As an optimization, the mass fraction of the ammonia solution in step (1) is 26% to 28%.
[0012] As an optimization, the preparation method of the ammonium aluminum sulfate solution in step (1) is: ammonium aluminum sulfate and deionized water are mixed evenly to prepare an ammonium aluminum sulfate solution with a molar concentration of 0.2 mol / L.
[0013] As an optimization, the programmed temperature increase in step (2) is to increase the temperature to 250°C at a rate of 10°C / h.
[0014] As an optimization, the high temperature calcination in step (2) is calcined at 900-1000° C. for 2-3 hours.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0016] When preparing high-purity nano-alumina, the present invention comprises the following steps: uniformly mixing an aqueous ammonium bicarbonate solution and polyethylene glycol, and adjusting the pH value to 9.3-9.4 with aqueous ammonia; dripping an ammonium aluminum sulfate solution into a reaction system, and then adjusting the pH value to 9.1-9.3 with aqueous ammonia; aging and filtering to obtain a precursor precipitate; uniformly mixing the precursor precipitate with anhydrous ethanol to prepare a precursor alcohol sol; placing the precursor alcohol sol in an autoclave, and performing supercritical drying to obtain a nano-alumina precursor; and calcining the nano-alumina precursor at a high temperature to obtain the high-purity nano-alumina.
[0017] The ammonium bicarbonate aqueous solution and polyethylene glycol are mixed evenly, and the pH is adjusted to 9.3-9.4 with ammonia water; the ammonium aluminum sulfate solution is added dropwise to the reaction system, and the pH is adjusted to 9.1-9.3 with ammonia water; the precursor precipitate is obtained after aging and filtering; the key to obtaining the NH4AlO(OH)HCO3 precursor is the NH4 + 、AlO(OH)2 - 、HCO3 - The concentration of NH4 must be large enough. During the reaction, the pH of the reaction system is adjusted to be greater than 9.0 with an aqueous ammonia solution so that the NH4 + 、AlO(OH)2 - 、HCO3 - The concentration of is maintained at a sufficiently high level, which is conducive to the formation of NH4AlO(OH)HCO3 precursor and improves the purity of the obtained nano-alumina. During the titration process, as the content of ammonium aluminum sulfate increases, the pH of the reaction system will gradually decrease. Therefore, after the addition is completed, the pH is adjusted with an ammonia solution to make the unreacted NH4 + 、AlO(OH)2 - 、HCO3 - The reaction continues to generate a precursor; this is conducive to further improving the purity of nano-alumina; the polyethylene glycol added to the reaction system acts as a dispersant, which can reduce the agglomeration phenomenon produced during the precipitation reaction, and the high-molecular surfactant polyethylene glycol is used to cover the surface of the precursor, making it difficult for the powders to agglomerate, thereby obtaining nano-scale and uniformly sized nano-alumina, further improving the purity of the nano-alumina. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Embodiment 1:
[0020] A preparation process of high-purity nano-alumina, the preparation process of high-purity nano-alumina comprising the following preparation steps:
[0021] (1) ammonium aluminum sulfate and deionized water are mixed evenly to prepare an ammonium aluminum sulfate solution with a molar concentration of 0.2 mol / L; ammonium bicarbonate and deionized water are mixed evenly to prepare an ammonium bicarbonate aqueous solution with a molar concentration of 2 mol / L; the ammonium bicarbonate aqueous solution and polyethylene glycol are mixed evenly at a mass ratio of 1:0.2, stirred at 10°C and 300 r / min for 10 min, adjusted the pH to 9.3 with a 26% ammonia aqueous solution, and added an ammonium aluminum sulfate solution with a mass fraction of 1.9 times that of the ammonium bicarbonate aqueous solution at a uniform rate within 20 min under the stirring conditions of 10°C and 500 r / min; after the titration is completed, the stirring is continued for 3 h, the pH is adjusted to 9.1 with a 26% ammonia aqueous solution, and aged for 25 h; filtered, washed with anhydrous ethanol and deionized water 5 times each to obtain a precursor precipitate;
[0022] (2) The precursor precipitate and anhydrous ethanol are mixed uniformly at a mass ratio of 1:2.0, and stirred at 10°C and 400r / min for 40min to obtain a precursor alcohol sol; the precursor alcohol sol is placed in an autoclave, and anhydrous ethanol is added to the autoclave to submerge it to 3 / 5 of the height of the steel pipe; the autoclave cover is covered, the air inlet pipe is connected to a nitrogen bottle, and the air outlet pipe is connected to a condenser, and nitrogen is passed to maintain the pressure at 7.4MPa, and then the gas is turned off; the inlet and outlet switches are tightened, the power of the temperature controller is turned on, and the temperature is programmed to rise to 250°C at a rate of 10°C / h, and the ethanol gas is slowly released after keeping the temperature for 30min, and then the dry gel in the autoclave is purged with nitrogen until it cools to room temperature, the autoclave is opened, and the material is discharged to obtain a nano-alumina precursor; the nano-alumina precursor is placed in a high-temperature resistance furnace, calcined at 900°C for 3h, and cooled to room temperature to obtain high-purity nano-alumina.
[0023] Embodiment 2:
[0024] A preparation process of high-purity nano-alumina, the preparation process of high-purity nano-alumina comprising the following preparation steps:
[0025] (1) ammonium aluminum sulfate and deionized water are mixed evenly to prepare an ammonium aluminum sulfate solution with a molar concentration of 0.2 mol / L; ammonium bicarbonate and deionized water are mixed evenly to prepare an ammonium bicarbonate aqueous solution with a molar concentration of 2 mol / L; the ammonium bicarbonate aqueous solution and polyethylene glycol are mixed evenly at a mass ratio of 1:0.21, stirred at 20°C and 400 r / min for 9 minutes, and the pH value is adjusted to 9.35 with a 27% ammonia aqueous solution. Under the stirring conditions of 20°C and 550 r / min, an ammonium aluminum sulfate solution with a mass twice that of the ammonium bicarbonate aqueous solution is added dropwise at a constant speed within 20 minutes; after the titration is completed, stirring is continued for 2.5 hours, and the pH value is adjusted to 9.2 with a 27% ammonia aqueous solution, and aged for 24 hours; filtered, washed with anhydrous ethanol and deionized water for 6 times each, to obtain a precursor precipitate;
[0026] (2) The precursor precipitate and anhydrous ethanol are mixed uniformly in a mass ratio of 1:2.1, and stirred at 20°C and 450r / min for 35min to obtain a precursor alcohol sol; the precursor alcohol sol is placed in an autoclave, and anhydrous ethanol is added to the autoclave to submerge it to 3 / 5 of the height of the steel pipe; the autoclave cover is covered, the air inlet pipe is connected to a nitrogen bottle, and the air outlet pipe is connected to a condenser, and nitrogen is passed to maintain the pressure at 7.5MPa, and then the gas is turned off; the air inlet and outlet switches are tightened, the power of the temperature controller is turned on, and the temperature is programmed to rise to 250°C at a rate of 10°C / h, and the ethanol gas is slowly released after keeping the temperature for 30min, and then the dry gel in the autoclave is purged with nitrogen until it cools to room temperature, the autoclave is opened, and the material is discharged to obtain a nano-alumina precursor; the nano-alumina precursor is placed in a high-temperature resistance furnace, calcined at 950°C for 2.5h, and cooled to room temperature to obtain high-purity nano-alumina.
[0027] Embodiment 3:
[0028] A preparation process of high-purity nano-alumina, the preparation process of high-purity nano-alumina comprising the following preparation steps:
[0029] (1) ammonium aluminum sulfate and deionized water are mixed evenly to prepare an ammonium aluminum sulfate solution with a molar concentration of 0.2 mol / L; ammonium bicarbonate and deionized water are mixed evenly to prepare an ammonium bicarbonate aqueous solution with a molar concentration of 2 mol / L; the ammonium bicarbonate aqueous solution and polyethylene glycol are mixed evenly at a mass ratio of 1:0.22, stirred at 30°C and 500 r / min for 8 minutes, and the pH value is adjusted to 9.4 with a 28% ammonia aqueous solution. Under the stirring conditions of 30°C and 600 r / min, an ammonium aluminum sulfate solution with a mass 2.1 times that of the ammonium bicarbonate aqueous solution is added dropwise at a constant speed within 20 minutes; after the titration is completed, stirring is continued for 2 hours, and the pH value is adjusted to 9.3 with a 28% ammonia aqueous solution, and aged for 23 hours; filtered, washed with anhydrous ethanol and deionized water for 7 times each, to obtain a precursor precipitate;
[0030] (2) The precursor precipitate and anhydrous ethanol are mixed uniformly in a mass ratio of 1:2.2, and stirred at 30°C and 500r / min for 30min to obtain a precursor alcohol sol; the precursor alcohol sol is placed in an autoclave, and anhydrous ethanol is added to the autoclave to submerge it to 3 / 5 of the height of the steel pipe; the autoclave cover is covered, the air inlet pipe is connected to a nitrogen bottle, and the air outlet pipe is connected to a condenser, and nitrogen is passed to maintain the pressure at 7.6MPa, and then the gas is turned off; the air inlet and outlet switches are tightened, the power of the temperature controller is turned on, and the temperature is programmed to rise to 250°C at a rate of 10°C / h, and the ethanol gas is slowly released after keeping the temperature for 30min, and then the dry gel in the autoclave is purged with nitrogen until it cools to room temperature, the autoclave is opened, and the material is discharged to obtain a nano-alumina precursor; the nano-alumina precursor is placed in a high-temperature resistance furnace, calcined at 1000°C for 2h, and cooled to room temperature to obtain high-purity nano-alumina.
[0031] Comparative Example 1:
[0032] The difference between the preparation process of high-purity nano-alumina in Comparative Example 1 and Example 2 lies in the difference in step (1), which is modified as follows: ammonium aluminum sulfate and deionized water are mixed evenly to prepare an ammonium aluminum sulfate solution with a molar concentration of 0.2 mol / L; ammonium bicarbonate and deionized water are mixed evenly to prepare an ammonium bicarbonate aqueous solution with a molar concentration of 2 mol / L; the ammonium bicarbonate aqueous solution and polyethylene glycol are mixed evenly at a mass ratio of 1:0.21, stirred at 20°C and 400 r / min for 9 minutes, adjusted to pH 9.35 with a 27% ammonia aqueous solution, and at 20°C and 550 r / min stirring conditions, ammonium aluminum sulfate solution twice the mass of the ammonium bicarbonate aqueous solution is added dropwise at a uniform speed within 20 minutes; after the titration is completed, stirring is continued for 2.5 hours and aging is carried out for 24 hours; filtering, washing with anhydrous ethanol and deionized water for 6 times each, to obtain a precursor precipitate. The remaining steps are the same as those in Example 2.
[0033] Comparative Example 2:
[0034] The preparation process of high-purity nano-alumina in Comparative Example 2 differs from that in Example 2 only in step (1), where step (1) is modified as follows: ammonium aluminum sulfate is mixed evenly with deionized water to prepare an ammonium aluminum sulfate solution with a molar concentration of 0.2 mol / L; ammonium bicarbonate is mixed evenly with deionized water to prepare an ammonium bicarbonate aqueous solution with a molar concentration of 2 mol / L; the ammonium bicarbonate aqueous solution and polyethylene glycol are mixed evenly at a mass ratio of 1:0.21, stirred at 20°C and 400 r / min for 9 min, and ammonium aluminum sulfate solution twice the mass of the ammonium bicarbonate aqueous solution is added dropwise at a constant speed within 20 min under stirring conditions of 20°C and 550 r / min; after the titration is completed, stirring is continued for 2.5 h, and aging is performed for 24 h; filtering is performed, and washing is performed 6 times with anhydrous ethanol and deionized water, respectively, to obtain a precursor precipitate. The remaining steps are the same as those in Example 2.
[0035] Comparative Example 3:
[0036] The preparation process of high-purity nano-alumina in Comparative Example 3 differs from that in Example 2 only in step (1), where step (1) is modified as follows: ammonium aluminum sulfate is mixed evenly with deionized water to prepare an ammonium aluminum sulfate solution with a molar concentration of 0.2 mol / L; ammonium bicarbonate is mixed evenly with deionized water to prepare an ammonium bicarbonate aqueous solution with a molar concentration of 2 mol / L; the ammonium bicarbonate aqueous solution is adjusted to pH 9.35 with a 27% ammonia aqueous solution, and an ammonium aluminum sulfate solution twice the mass of the ammonium bicarbonate aqueous solution is added dropwise at a constant speed within 20 minutes at 20°C and 550 r / min stirring conditions; after the titration is completed, stirring is continued for 2.5 hours, and the pH is adjusted to 9.2 with a 27% ammonia aqueous solution, and aged for 24 hours; filtering, washing with anhydrous ethanol and deionized water for 6 times each, to obtain a precursor precipitate. The remaining steps are the same as those in Example 2.
[0037] Test Case
[0038] Purity testing
[0039] Test method: The purity of the examples and comparative examples was tested according to GB / T24487. The results are shown in Table 1.
[0040] Table 1
[0041] purity(%) purity(%) Example 1 98.15 Comparative Example 1 90.57 Example 2 98.41 Comparative Example 2 82.38 Example 3 98.26 Comparative Example 3 92.64
[0042] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the high-purity nano-alumina prepared by the present invention has a higher purity.
[0043] By comparison, the purity of Examples 1 to 3 is greater than that of Comparative Examples 1 to 2, indicating that the ammonium bicarbonate aqueous solution and polyethylene glycol are uniformly mixed, and the pH is adjusted to 9.3 to 9.4 with aqueous ammonia; an ammonium aluminum sulfate solution is added dropwise to the reaction system, and the pH is adjusted to 9.1 to 9.3 with aqueous ammonia; a precursor precipitate is obtained after aging and filtration; the key to obtaining the NH4AlO(OH)HCO3 precursor is that NH4 + 、AlO(OH)2 - 、HCO3 - The concentration of NH4 must be large enough. During the reaction, the pH of the reaction system is adjusted to be greater than 9.0 with an aqueous ammonia solution so that the NH4 + 、AlO(OH)2 - 、HCO3 - The concentration of is maintained at a sufficiently high level, which is conducive to the formation of NH4AlO(OH)HCO3 precursor and improves the purity of the obtained nano-alumina. During the titration process, as the content of ammonium aluminum sulfate increases, the pH of the reaction system will gradually decrease. Therefore, after the addition is completed, the pH is adjusted with an ammonia solution to make the unreacted NH4 + 、AlO(OH)2 - 、HCO3 - Continue to react to generate a precursor; this is conducive to further improving the purity of nano-alumina.
[0044] By comparison, the purity of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that the polyethylene glycol added to the reaction system acts as a dispersant, which can reduce the agglomeration phenomenon produced during the precipitation reaction. The polymer surfactant polyethylene glycol is used to cover the surface of the precursor, making it difficult for the powders to agglomerate, thereby obtaining nano-alumina with nanoscale and uniform particle size, further improving the purity of the nano-alumina.
[0045] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A preparation process of high-purity nano-alumina, characterized in that: The preparation process of the high-purity nano-alumina comprises the following steps: uniformly mixing an aqueous solution of ammonium bicarbonate and polyethylene glycol, and adjusting the pH to 9.3-9.4 with aqueous ammonia; dripping an ammonium aluminum sulfate solution into the reaction system, and then adjusting the pH to 9.1-9.3 with aqueous ammonia; aging and filtering to obtain a precursor precipitate; uniformly mixing the precursor precipitate with anhydrous ethanol to prepare a precursor alcohol sol; The precursor alcohol sol is placed in a high pressure autoclave and subjected to supercritical drying to obtain a nano-alumina precursor; the nano-alumina precursor is calcined at a high temperature to obtain high-purity nano-alumina.
2. The preparation process of high-purity nano-alumina according to claim 1, characterized in that: The preparation process of the high-purity nano-alumina comprises the following preparation steps: (1) Mixing ammonium bicarbonate aqueous solution and polyethylene glycol in a mass ratio of 1:(0.2-0.22), stirring at 10-30° C. and 300-500 r / min for 8-10 min, adjusting the pH to 9.3-9.4 with an ammonia solution, and adding aluminum ammonium sulfate solution 1.9-2.1 times the mass of the ammonium bicarbonate aqueous solution dropwise at a constant rate within 20 min at 10-30° C. and 500-600 r / min; after the titration is completed, stirring is continued for 2-3 h, adjusting the pH to 9.1-9.3 with an ammonia solution, and aging for 23-25 h; filtering, washing with anhydrous ethanol and deionized water for 5-7 times each, to obtain a precursor precipitate; (2) The precursor precipitate and anhydrous ethanol are mixed uniformly in a mass ratio of 1:(2.0-2.2), and stirred at 10-30°C and 400-500r / min for 30-40min to obtain a precursor alcohol sol; the precursor alcohol sol is placed in an autoclave, and anhydrous ethanol is added to the autoclave to submerge it to 3 / 5 of the height of the steel pipe; the autoclave cover is covered, the air inlet pipe is connected to a nitrogen bottle, and the air outlet pipe is connected to a condenser, and nitrogen is passed to maintain the pressure at 7.4-7.6MPa, and then the gas is turned off; the air inlet and outlet switches are tightened, the power of the temperature controller is turned on, and the temperature is programmed to rise. After keeping the temperature for 30min, the ethanol gas is slowly released, and then the dry gel in the autoclave is purged with nitrogen until it cools to room temperature, the autoclave is opened, and the material is discharged to obtain a nano-alumina precursor; the nano-alumina precursor is placed in a high-temperature resistance furnace, calcined at high temperature, and cooled to room temperature to obtain high-purity nano-alumina.
3. The preparation process of high-purity nano-alumina according to claim 2, characterized in that: The preparation method of the ammonium bicarbonate aqueous solution in step (1) is: ammonium bicarbonate and deionized water are mixed evenly to prepare an ammonium bicarbonate aqueous solution with a molar concentration of 2 mol / L.
4. The preparation process of high-purity nano-alumina according to claim 2, characterized in that: The polyethylene glycol in step (2) is prepared by mixing two polyethylene glycols, PEG400 and PEG6000, in a mass ratio of 1:
1.
5. The preparation process of high-purity nano-alumina according to claim 2, characterized in that: The mass fraction of the ammonia solution in step (1) is 26% to 28%.
6. The process for preparing high-purity nano-alumina according to claim 2, characterized in that: The preparation method of the ammonium aluminum sulfate solution in step (1) is: mixing ammonium aluminum sulfate and deionized water evenly to prepare an ammonium aluminum sulfate solution with a molar concentration of 0.2 mol / L.
7. The process for preparing high-purity nano-alumina according to claim 2, characterized in that: The programmed temperature rise in step (2) is to increase the temperature to 250°C at a rate of 10°C / h.
8. The process for preparing high-purity nano-alumina according to claim 2, characterized in that: The high temperature calcination in step (2) is calcination at 900-1000° C. for 2-3 hours.